Integration of Geology, Hydrogeology and Geomorphology for Groundwater Occurrence in A Hard Rock Region from Parts of Nalgonda District, Telangana State, India, Using Remote Sensing and G.I.S Techniques - M.Ganesh, K; Jagannadha Rao, M; Jai Sankar, G; K.S.K. Sai Vadapalli, V (International Journal of Engineering and Technology, 2018)
The study area is located in and around Nalgonda town in Nalgonda district, Telangana state.Â For the detailed investigation of the groundwater condition of a part of this district and covers an area of about 2880 sq.km. in Narkatpalli, Chityal, Katangur, Nakrekaletc. mandals have been selected. Survey of India toposheets on 56 0/4, 0/8, P/1, P/5, Scale - 1: 50,000, IRS ID LISS III satellite imagery using remote sensing and G.I.S. techniques.Â A detailed study is carried out by classifying the wells into four categories.Â Â The groundwater regime with reference to depth water table fluctuation has been evaluated in the study area.Â The deeper wells mainly occur or observed to occur in the central and southeastern parts of the study area whereas the shallow wells are confined to northern, eastern and southeastern parts of the study area.Â Also the drainage pattern is observed as medium to coarse textured and dendritic to subdendritic type, which is characteristic of hard rock terrain and develops in regions of homogeneity.Â Â The field data provides the information about the depth to water table, and fluctuation of the groundwater.Â Â The best suitable areas identified were mainly in shallow valley fill is mostly composed of sandy material, which are generally good to excellent of groundwater prospects.Â Most of the area posed good groundwater recharge capacity.Â Based on these studies on lineament density map of the entire study area has been prepared indicating areas of high, moderate and low density lineaments.Â The important observation is that the deeper wells are having low fluctuation whereas the shallow wells are characterised by high fluctuation and high density lineaments.Â To study the hydrogeological conditions in the area, field investigations were carried out and 94 wells were inventoried.Â Groundwater occurs in the study area under water table and semi-confined conditions limited to weathered and fractured zones.Â The zone of weathering ranges from 0 m (near inselbergs) to 17 m.Â The joints and fractures, which act as conduits for the movement of groundwater are responsible for the good yield of water from the wells.Â